BOARD SIZE, BOARD INDEPENDENCE, INSTITUSIONAL OWNERSHIP AND INTERNAL CONTROL DISCLOSURE - Raka Bagaskara; Totok Dewayanto (Diponegoro Journal of Accounting, 2018)
This study aims to exmine the effect of board size, board independence, and institusional ownership as independent variable toward internal control disclosure as dependent variable.This study uses secondary data obtained from the Indonesia stock exchange (idx). This research using a sample as many as 354 manufacturing companies registered in BEI year 2014 – 2016. The methods used in this research is purposive sampling method. Statistical techniques used in this study is a multiple regression.The results obtained from this research shows the board size, and board independence have a significant positive influence on internal control and disclosure. Then the institusional ownership have a significant negative influence on the internal control and disclosure.